Footprints of the Nursing Profession : Current Trends and Emerging Issues in Ghana - Naab, Florence; Korsah, Kwadwo Ameyaw; Kwashie, Adzo; Aziato, Lydia (Clinical sciences series (Accra, Ghana) ;, 2014)
The Reader contains educative and exciting chapters centred on the nursing profession and research areas of faculty members in Ghana. The target readers are nursing students of all categories, nurse educators, administrators, clinicians, and researchers locally and internationally.